Field research 2009 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2009)
Includes research reports from these locations: East Central Kansas Experiment Field, Kansas River Valley Experiment Field, Harvey County Experiment Field, Irrigation and North Central Kansas Experiment Fields, South Central Kansas Experiment Field, and Western Kansas Agricultural Research Centers.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1017; Kansas Agricultural Experiment Station contribution; no. 09-225-S; Kansas; Agriculture; Crops; Weed control; Disease control; Fertilizer; Irrigation